Kinerja Pegawai Dinas Sosial Pemberdayaan Perempuan Dan Perlindungan Anak Kabupaten Luwu Timur - Nuryani, Depi; Muhammadiah, Muhammadiah; Usman, Jaelan (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out how the formance of The Social Servise for Women Impowerment and Child Protection in East Luwu Regency in committing acts of violence that occurred. The method used qualitativeresearch. Research used data interview techniques through 10 informants. The results showed that the performance of the Social Servise for Women’s Emporwerment and Child duties was efficient,but the formance was not effective, for complaint, mentoring, case referrals, legal assistance and repatriation / protection still had a lot of supervisions. It seen from the cases of violence every year were increasing because it was understanding to prevent violence againt Women and Childern. So that in this case the government and society were very important in preventing acts of violence against women and children in East Luwu Regency. Keywords: Employee Performance, Woman Empowerment, Child Protection.This study purposed to find out how the formance of The Social Servise for Women Impowerment and Child Protection in East Luwu Regency in committing acts of violence that occurred. The method used qualitativeresearch. Research used data interview techniques through 10 informants. The results showed that the performance of the Social Servise for Women’s Emporwerment and Child duties was efficient,but the formance was not effective, for complaint, mentoring, case referrals, legal assistance and repatriation / protection still had a lot of supervisions. It seen from the cases of violence every year were increasing because it was understanding to prevent violence againt Women and Childern. So that in this case the government and society were very important in preventing acts of violence against women and children in East Luwu Regency. Keywords: Employee Performance, Woman Empowerment, Child Protection.